Low circulation of respiratory syncytial and influenza viruses during autumn-winter 2021 in the industrial workplace and long-term healthcare facilities in Athens, Greece - Papachristou, Eleni; Rokka, Chrysoula; Sotiriadou, Triantafyllia; Maneka, Leukothea; Vassilakis, Alexandros; Sapounas, Spyros; Paraskevis, Dimitrios; Jahaj, Eddison; Kotanidou, Anastasia; Lagiou, Pagona; Magiorkinis, Gkikas (Frontiers in Medicine, 2023)
The emergence of SARS-CoV-2 has pinpointed the importance of Non-Pharmaceutical Interventions (NPIs), which have been traditionally used for the prevention of the spread of respiratory viruses among individuals. The aim of our study was to capture the level of circulation of Respiratory Syncytial and Influenza viruses during a period of medium severity NPIs due to SARS CoV-2 pandemics in Greece. A total of 2225 nasopharyngeal samples were received during the year 2021 as part of the routine diagnostic service and were divided into two study groups: a) January to September 2021 and b) October till the end of December 2021. The latter is the time of the year where there is a peak of infections from most respiratory viruses and thus most of the samples were tested in that period. The samples were taken from three different sites i.e., a) industrial workers in a factory b) elderly home care facilities and c) people that actively asked to be tested for SARS CoV-2. All the samples were tested simultaneously for SARS CoV2, RSV and Influenza Virus. 2110 samples were negative for either of the three viruses, 106 were SARS CoV2 positive and 9 were RSV positive from which the 7 were found in the workers’ group. None of the samples was found to be positive for influenza Virus and no sample had co-infection. Our work show low level circulation of RSV and influenza viruses during autumn-winter 2021 and will provide a reference for future studies of RSV and influenza in Greece